(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Data on landslide locations in the Podsljeme area can be found in three historical landslide inventory maps. Inventory maps from 1979 and 2007 are made based on geomorphological field mapping and historical records while an inventory map from 2017, compiled for the study area (21 km2), is based on LiDAR data acquired in December 2013. A comparison of three landslide inventory maps was performed with three tests based on landslide statistics, frequency-area distribu- tion, geographical discrepancy of landslides and landslide density maps. The results show significant differences in the number of identified landslides as well as in the size and distribution of landslides. A comparison of inventories also showed the unreliability of the existing historical inventories and usefulness of LiDAR data for preparation of complete landslide inventory maps. LiDAR-based inventory for the Podsljeme area could be a valuable tool for a wide range of users i.e., decision-makers, land developers and environmental and civil defense agencies. It is also necessary for landslide susceptibility and hazard mapping, which is a prerequisite for landslide risk reduction.